Competitive Promotional Tools & Retailing - The Game where you differentiate or Die - Memon, Sharif (Indian Journal of Marketing, 2007)
The recent trends in India demonstrate that retailing is emerging steadily as an organized sector, with a variety of big business players trying their kismets in this part and thereby expanding into retailing. The best instances are Tatas, Reliance, RPG, Adanis and the list persists. This sector appears to grip a major place in the economy of the country in the future to come. Retailing is the final movement in the value chain of the product that is noticeably classified to be a service. The Indian retail Industry is shaped of with retail players like Food retailers, Health and beauty goods retailers, Clothing etc. Also it gives the organized retail formats in India like Hypermarket, supermarket, specialty retailing stores etc.The competitive promotional tools include all the tools starting from the Advertising, Sales promotions, Direct Marketing, Personal selling, Public Relations, Publicity, Interactive marketing, and point of purchase marketing. The study focuses on three Retail chains viz. Big Bazaar, Adani and Star India Bazaar.